1989
DOI: 10.1259/0007-1285-62-743-995
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian failure following abdominal irradiation in childhood: the radiosensitivity of the human oocyte

Abstract: Ovarian function has been studied sequentially since 1975 in 19 patients treated in childhood for an intra-abdominal tumour with surgery and whole abdominal radiotherapy (total dose 30 Gy). Eleven patients received chemotherapeutic agents that are not known to cause gonadal dysfunction. All but one patient have developed ovarian failure with persistently elevated gonadotrophin levels (FSH and LH greater than 32 IU/litre) and low serum oestradiol values (less than 40 pmol/litre) before the age of 16 years. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
6

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(94 citation statements)
references
References 14 publications
1
87
0
6
Order By: Relevance
“…The LD50 (the radiation dose causing the death of 50 per cent of cells) for the human oocyte has been estimated to be less than 4Gy (Wallace et al, 1989b). Therefore it is not surprising that a high prevalence of primary ovarian failure is found after TBI.…”
Section: Ovarymentioning
confidence: 99%
“…The LD50 (the radiation dose causing the death of 50 per cent of cells) for the human oocyte has been estimated to be less than 4Gy (Wallace et al, 1989b). Therefore it is not surprising that a high prevalence of primary ovarian failure is found after TBI.…”
Section: Ovarymentioning
confidence: 99%
“…However, it should be noted that in addition to chemical treatment during adulthood, mice in the RACB studies were exposed during prenatal and early postnatal development when follicles are more susceptible to toxicants than in the adult . Given the relative resistance of human primordial follicles in comparison to rodents (Wallace et al, 1989), it is apparent that further work will be required to evaluate whether or not human and murine follicle counts respond in a comparable fashion to reproductive toxicants.…”
Section: Discussionmentioning
confidence: 99%
“…In 1950 Duffy and Fitzgerald1l reported that 9 of a series of 28 children with thyroid carcinoma had received irradiation for thymic enlargement previously, and raised the possibility that irradiation was an aetiological factor in the development of thyroid tumours. Subsequently large-scale surveys were undertaken, all of which confirmed unequivocally a causal relationship between external irradiation of the neck in childhood and thyroid cancer.…”
Section: Thyroid Cancermentioning
confidence: 99%